2015
DOI: 10.1186/s12959-015-0045-1
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable regression of massive deep vein thrombosis in response to intensive oral rivaroxaban treatment

Abstract: Deep vein thrombosis (DVT) is a common disease and is associated with pulmonary embolism (PE). Proximal iliofemoral DVT may lead to severe PE and chronic venous insufficiency. The standard therapy for DVT is anticoagulant therapy using heparin and a vitamin K antagonist, but a recent clinical study showed that rivaroxaban, an oral Xa inhibitor, was comparable to standard therapy and had less bleeding complications. Intensive high-dose anticoagulation is recommended during the initial 3 weeks of DVT treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Earlier studies using repeated phlebographic examinations considered recanalization to be a later development, occurring over periods varying from 6 months to 1 years after the acute event. 32 However, current reports from many different authors, 13,14 and also our study, show that recanalization of thrombi in lower limb DVT in patients on DOACs can be faster than expected. In these cases, CDU is a valid and noninvasive tool, not only for initial diagnosis of DVT, but also for evaluation of the long term result, and can be used to guide initial patient management, providing information on adherence of the clot to the vein wall and on recanalization.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Earlier studies using repeated phlebographic examinations considered recanalization to be a later development, occurring over periods varying from 6 months to 1 years after the acute event. 32 However, current reports from many different authors, 13,14 and also our study, show that recanalization of thrombi in lower limb DVT in patients on DOACs can be faster than expected. In these cases, CDU is a valid and noninvasive tool, not only for initial diagnosis of DVT, but also for evaluation of the long term result, and can be used to guide initial patient management, providing information on adherence of the clot to the vein wall and on recanalization.…”
Section: Discussionmentioning
confidence: 60%
“…11,12 Some reports have demonstrated that DOACs have the capacity to stimulate regression of thrombi, whether in the venous system or in other locations, such as the cardiac chambers. 13,14 However, with regard to recanalization, few studies have compared ultrasonographic findings from patients treated with DOACs or warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…There is one report of successful treatment of IVCS with rivaroxaban (30 mg → 15 mg daily) [24]. This case report adds to the literature by demonstrating that single-dose edoxaban (30 mg daily) without acute-phase parenteral anticoagulation is also effective though long-term follow-up is still required.…”
Section: Discussionmentioning
confidence: 84%
“…45) After initial treatment with UFH followed by 21 days of rivaroxaban (15 mg bid), an MDCT scan showed almost complete thrombus regression, with only a small thrombus remaining at the left popliteal vein. 45) The patient was then switched to rivaroxaban 15 mg once-daily and, after 12 months of treatment, no bleeding or recurrent venous thromboembolic events were observed. The outcomes of this case support the results of the J-EINSTEIN study, in which an initial, intensive 21-day regimen with rivaroxaban was shown to be an effective choice for the treatment of DVT.…”
Section: )mentioning
confidence: 95%
“…In a 77-year-old patient with massive DVT accompanied by proximal iliofemoral vein thrombus and iliac vein compression syndrome, there was substantial thrombus regression within the initial 3-week period after administration of rivaroxaban. 45) In a patient with residual vein thrombosis after warfarin treatment for right common femoral vein thrombosis, a switch to rivaroxaban therapy for 3 months (plus 3 weeks at the high dose) achieved complete DVT resolution. 46) Extensive DVT has also been successfully treated to a point of complete thrombus resolution, with 5 days of subcutaneous fondaparinux treatment followed by 6 months of 60 mg once-daily edoxaban.…”
Section: Real-world Data On the Use Of Non-vitamin K Antagonist Oral mentioning
confidence: 98%